2020
DOI: 10.7554/elife.50803
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus protein m154 perturbs the adaptor protein-1 compartment mediating broad-spectrum immune evasion

Abstract: Cytomegaloviruses (CMVs) are ubiquitous pathogens known to employ numerous immunoevasive strategies that significantly impair the ability of the immune system to eliminate the infected cells. Here, we report that the single mouse CMV (MCMV) protein, m154, downregulates multiple surface molecules involved in the activation and costimulation of the immune cells. We demonstrate that m154 uses its cytoplasmic tail motif, DD, to interfere with the adaptor protein-1 (AP-1) complex, implicated in intracellular protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Alternatively, the presence in SMCMV of additional viral products interfering with the CD48:2B4 axis could have made the conservation of S30 s capacity to interact with 2B4 redundant. In this connection, we have reported that murine CMV encodes a viral protein, m154, that reduces CD48 levels at the cell surface of infected cells, and showed in a mouse model that the viral protein promotes viral growth by subverting NK cell responses [63,64]. Similarly, we found that in HCMV-infected macrophages, CD48 is downregulated [65], although in this case, the HCMV protein involved and the consequences of these effects remain to be defined.…”
Section: Discussionmentioning
confidence: 72%
“…Alternatively, the presence in SMCMV of additional viral products interfering with the CD48:2B4 axis could have made the conservation of S30 s capacity to interact with 2B4 redundant. In this connection, we have reported that murine CMV encodes a viral protein, m154, that reduces CD48 levels at the cell surface of infected cells, and showed in a mouse model that the viral protein promotes viral growth by subverting NK cell responses [63,64]. Similarly, we found that in HCMV-infected macrophages, CD48 is downregulated [65], although in this case, the HCMV protein involved and the consequences of these effects remain to be defined.…”
Section: Discussionmentioning
confidence: 72%
“…To directly test the hypothesis, we used an MCMV with a deletion in this gene (MCMVΔm138). As illustrated in Figure 2B , during infection of IC-21 cells with MCMVΔm138, cell surface expression of ICOSL was maintained to levels similar to mock-infected cells, while the levels of CD84, a molecule targeted by the MCMV m154 protein ( Strazic Geljic et al, 2020 ), used as a control, markedly decreased. These effects were not due to a growth defect of the mutant virus in IC-21 cells, as indicated in earlier studies where comparable multi-step growth kinetics between an MCMV deleted in m137-m139 and parental MCMV were observed ( Cavanaugh et al, 1996 ).…”
Section: Resultsmentioning
confidence: 94%
“…For instance, MCMV produces the multifaceted immunomodulatory protein m152, which is capable of downregulating MHC class I molecules and different RAE-1 isoforms, as well as modulating the cGAS-STING pathway, thereby evading type I IFN-, NK-, and T cell-dependent immune responses to MCMV infection ( Fink et al, 2013 ; Krmpotic et al, 1999 ; Lodoen et al, 2003 ; Stempel et al, 2019 ; Ziegler et al, 1997 ). Moreover, we have recently demonstrated that by interfering with AP-1-mediated protein sorting, the m154 glycoprotein targets a broad-spectrum of cell surface molecules implicated in the antiviral NK and T-cell responses ( Strazic Geljic et al, 2020 ; Zarama et al, 2014 ). In HCMV, this concept is best exemplified by the US12 family, whose members, as it will be discussed below, have been reported to alter the expression of numerous plasma membrane proteins, mainly NK ligands, adhesion proteins and cytokine receptors ( Fielding et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides m152, the object of our investigation here, more prominent examples affected by the deletion include m145 and m155 that downmodulate NKG2D ligands MULT-1 (Krmpotic et al, 2005 ) and H60 (Hasan et al, 2005 ), respectively, the activatory ligand m157 of the Ly49H NK cell subset that confers genetic resistance to mCMV by controlling early virus replication in C57BL/6 (haplotype H-2 b ) mice (Arase et al, 2002 ; Scalzo et al, 2003 ; Voigt et al, 2003 ; Bubić et al, 2004 ; Fodil-Cornu et al, 2008 ), m154 that reduces the cell-surface expression of the SLAM family member CD48 (Zarama et al, 2014 ) and mediates broad-spectrum immune evasion by perturbing the adaptor protein-1 compartment (Strazic Geljic et al, 2020 ), and m147.5 that downmodulates the co-stimulatory molecule CD86/B7-2 on antigen-presenting cells (Loewendorf et al, 2004 ). So, obviously, a phenotype of mutant virus mCMV-Δm06 W cannot be attributed with any certainty to the deletion of m06.…”
Section: Resultsmentioning
confidence: 99%